Pelaksanaan Program Bidang Keagamaan di MTsN 10 Tanah Datar - Susi Aslama sus; Rizki Pebrina; Abhanda Amra; T. Idris (SURAU : Journal of Islamic Education, 2024)
AbstractThis research aims to see how the religious sector program is implemented at MTsN 10 Tanah Datar Nagari Sungayang, Tanah Datar Regency, which consists of program planning, program implementation and program evaluation. The type of research used is qualitative research with qualitative descriptive methods. Data collection techniques through observation, interviews and documentation techniques were carried out at MTsN 10 Tanah Datar. The research results show that the implementation of religious programs at MTsN 10 Tanah Datar consists of two aspects. In the Al-Qur'an khatam program aspect, planning is carried out by making an implementation schedule and determining the verses that will be read by students and teachers. The implementation of the Al-Qur'an khatam program involves gathering students and all teachers in the field. As well as the evaluation carried out, each teacher is given the task of controlling all students whether all students are reading or not. In the planning aspect of the tahajjud movement program, the teacher created a WhatsApp group to control the tahajjud. During the implementation of the tahajjud movement program, the class teacher together with the parents reminded and woke up the students to perform the tahajjud prayer. As well as evaluations carried out, namely by conducting daily evaluations by checking students' Tahajjud prayers, monthly by way of the class teacher and homeroom teacher's assistant recording the number of students' prayers for one month, and every semester a meeting is held with the student's parents. AbstrakPenelitian ini bertujuan untuk melihat bagaimana pelaksanaan Program Bidang keagamaan Di MTsN 10 Tanah Datar Nagari Sungayang Kabupaten Tanah Datar yang terdiri dari perencanaan program, pelaksanaan program dan evaluasi program. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan metode deskriptif kualitatif. Teknik pengumpulan data melalui teknik observasi, wawancara, dan dokumentasi yang dilakukan di MTsN 10 Tanah Datar. Hasil penelitian menunjukkan bahwa pelaksanaan program keagamaan di MTsN 10 Tanah Datar terdiri dari dua aspek. Pada aspek program khatam Al-Qur’an perencanaan dilakukan dengan membuat jadwal pelaksanaan dan menetapkan potongan ayat yang akan dibaca oleh siswa dan guru. Untuk pelaksanaan program khatam Al-Qur’an yaitu dengan mengumpulkan siswa dan seluruh guru di lapangan. Serta evaluasi yang dilakukan yaitu setiap guru diberikan tugas untuk mengontrol seluruh siswa apakah seluruh siswa ikut membaca atau tidak. Pada aspek program gerakan tahajjud perencanaan yang dilakukan yaitu guru membuat group whatsapp untuk mengontrol tahajjud. Pada pelaksanaan program gerakan tahajjud wali kelas bersama orang tua mengingatkan dan membangunkan siswa untuk melaksanakan sholat tahajjud. Serta evaluasi yang dilakukan yaitu dengan melakukan evaluasi harian dengan mengecek sholat tahajjud siswa, bulanan dengan cara wali kelas dan pendamping wali kelas merekap jumlah sholat siswa selama satu bulan, dan setiap semester diadakan rapat dengan wali murid.